1985
DOI: 10.5006/1.3582983
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitrogen on the Sensitization of AISI 304 Stainless Steel

Abstract: Thermodynamic calculations have been used to construct time temperature sensitization (TTS) diagrams for AISI 304 stainless steels (SS). The quantitative Stawstrom and Hillert model, which is based on chromium diffusion control of sensitization, was used to calculate the TTS diagrams. Electrochemical potentiokinetic reactivation (EPR) tests were performed on these steels, with various nitrogen additions, to obtain the experimental TTS curves. The calculated and experimental TTS diagrams have been compared to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 6 publications
2
24
0
1
Order By: Relevance
“…Similarly, alloys with higher Cr contents are more resistant to sensitization as time to Cr depletion at the grain boundaries is shifted to longer duration ( Ref 28). The beneficial effects of N on the sensitization have been observed in many studies ( Ref 3,14,25,26,29), and the retardation of sensitization by N has been confirmed for alloys with N up to 0.16 wt.% ( Ref 27,28). In the present alloys, subsequent to Cr 23 C 6 precipitation, the grain boundary Cr depletion can be delayed by the presence of N. Nitrogen is known to retard the nucleation and growth of Cr 23 C 6 precipitation and changes the activity of Cr in equilibrium with the carbide (Ref [26][27][28][29].…”
Section: Intergranular Corrosion Resistancementioning
confidence: 75%
See 1 more Smart Citation
“…Similarly, alloys with higher Cr contents are more resistant to sensitization as time to Cr depletion at the grain boundaries is shifted to longer duration ( Ref 28). The beneficial effects of N on the sensitization have been observed in many studies ( Ref 3,14,25,26,29), and the retardation of sensitization by N has been confirmed for alloys with N up to 0.16 wt.% ( Ref 27,28). In the present alloys, subsequent to Cr 23 C 6 precipitation, the grain boundary Cr depletion can be delayed by the presence of N. Nitrogen is known to retard the nucleation and growth of Cr 23 C 6 precipitation and changes the activity of Cr in equilibrium with the carbide (Ref [26][27][28][29].…”
Section: Intergranular Corrosion Resistancementioning
confidence: 75%
“…These include the local buffering effect of N by formation of either NH 3 , NH 4 + , NO 3 + , nitride, etc., N impending active dissolution, enrichment in passive film, barrier layer, N-Mo synergism, N retarding Cr 23 C 6 precipitation, ferrite and deformationinduced a¢ and e, etc. ( 10,17,[26][27][28]38,39). However, based on the above observation, it can be summarized that the indigenously developed type 301LN stainless steel possesses better corrosion resistance compared to imported grade in chloride environment.…”
Section: Potentiodynamic Anodic Polarization Studiesmentioning
confidence: 99%
“…In some of the studies [31,32] it has been reported that presence of nitrogen in type 304 austenitic SS results in earlier crack initiation and higher CGR in boiling magnesium chloride solution. It has also been reported that nitrogen addition up to 0.16 wt.% reduces susceptibility to IGSCC in sensitised type 304 stainless steel in sodium sulphate added water at 250°C [29]. This behaviour was attributed to the retarding effect of nitrogen on the sensitization kinetics when nitrogen is present in the range of 0.04-0.16 wt.% [28,29].…”
Section: Introductionmentioning
confidence: 92%
“…Problems due to LTE are expected to be less in type 304L stainless steel making it suitable for use in reactors with a long design life [25,27]. Nitrogen addition to SS has been shown to increase its resistance to sensitization but the extent of beneficial effect varies in type 304L and 316L stainless steels [23,28,29]. The sensitisation behaviour as a function of nitrogen content and its effect on IGSCC crack growth rate (CGR) in simulated BWR environment for type 304LN stainless steel thus needs to be established.…”
Section: Introductionmentioning
confidence: 98%
“…The essential feature of this model is consideration of the chromium diffusion rate as established by the chromium thermodynamic activity gradient between the activity of chromium in the bulk and that at the carbide-austenite interface. This model considers temperature, strain, and compositional effects in materials (Mozhi et al, 1985).…”
Section: Alloying Effects Onlgscc Susceptibilitymentioning
confidence: 99%